# Solve for m y=( log of 2-m)/( square root of 2m+3)

y=log(2-m)2m+3
Rewrite the equation as log(2-m)2m+3=y.
log(2-m)2m+3=y
Cross multiply.
Cross multiply by setting the product of the numerator of the right side and the denominator of the left side equal to the product of the numerator of the left side and the denominator of the right side.
y⋅(2m+3)=log(2-m)
Multiply y by 2m+3.
y2m+3=log(2-m)
y2m+3=log(2-m)
To remove the radical on the left side of the equation, square both sides of the equation.
(y2m+3)2=log2(2-m)
Simplify the left side of the equation.
(y)2(2m+3)=log2(2-m)
Solve for m.
Simplify the left side.
Apply the distributive property.
y2(2m)+y2⋅3=log2(2-m)
Reorder.
Rewrite using the commutative property of multiplication.
2y2m+y2⋅3=log2(2-m)
Move 3 to the left of y2.
2y2m+3y2=log2(2-m)
2y2m+3y2=log2(2-m)
2y2m+3y2=log2(2-m)
Subtract log2(2-m) from both sides of the equation.
2y2m+3y2-log2(2-m)=0
Subtract 3y2 from both sides of the equation.
2y2m-log2(2-m)=-3y2
2y2m-log2(2-m)=-3y2
Solve for m y=( log of 2-m)/( square root of 2m+3)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top